Library Visitor Noise Monitoring System Design With Warning Using LED and Telegram - Nur Fitriani; Sitti Ahmiatri Saptari; Elvan Yuniarti (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2023)
Abstract. The library supports education and is used as a place to learn and gain knowledge. To maximize its use, visitors need comfort by not making noise or upheaval that can disturb other visitors. According to the decision of the Ministry of Environment in 1996, the maximum standard for noise levels in libraries is 55 dB. This research was conducted to design a tool that can monitor the noise that occurs in the library by providing information on room conditions usingLED (Light Emitting Diode) lights, LCD (Liystal Displayquid Cr), and giving notifications to librarians in the form of messages on the Telegram application if the noise exceeds the limit. maximum. The tool is designed using ESP32 as a control, a GY-MAX4466 sensor to detect sound, and the output system uses red, yellow, and greenLED (Light Emitting Diode), LCD (Liquid Crystal Display) 16x2, and the Telegram application. The results of this study concluded that the noise monitoring system was running well, with a GY-MAX4466 sensor error rate of 0.4%, and the best R Square value was obtained at a distance of 1 meter from the sound source with an R Square value of 0,7202.